KEEFEKTIFAN MEDIA PEMBELAJARAN NEARPOD TERHADAP HASIL BELAJAR SISWA KELAS 4 SDN MACANAN 1 PADA MATERI PERUBAHAN WUJUD ZAT - Saputri, Aulia; Sahari, Sutrisno; Nursalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The science learning process (IPAS) in Grade 4 at SDN Macanan 1 still relies solely on textbooks as the main learning resource, resulting in low student engagement and difficulty in understanding the material, particularly the topic of changes in the states of matter. Based on observations and interviews, only 13 out of 40 students met the Minimum Mastery Criteria (KKTP) score of 75. This study aims to determine the effectiveness of using Nearpod-based instructional media to improve students' learning outcomes. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 40 fourth-grade students, and the data were collected through observation, interviews, and learning outcome tests. The instructional media were tested in both limited and wider trials. The limited trial showed a mastery level of 80%, while the wider trial showed 86.6%. These results indicate that the Nearpod-based instructional media are highly effective in improving students’ learning outcomes, exceeding the KKTP score, and can be implemented without any revisions.